Kesenjangan Metodologis dalam Tafsir Mahasin Al-Ta’wil - Melani Novita Anggraini; Hanik Rosyida; Yusuph Dauda Gambari (Lajnah Pentashihan Mushaf Al-Qur'an, 2026)
This study examines the consistency and methodological implications of isra’iliyyat in Tafsir Mahasin at-Ta’wil by al-Qasimiy within a contemporary context, focusing on the aspect of methodological consistency that remains relatively understudied. The problem addressed is the extent to which al-Qasimiy is consistent in applying the rules for using isra’iliyyat in his tafsir practice, as well as its methodological implications for the development of tafsir studies. This research employs a qualitative approach using descriptive-analytical and critical analysis methods through library research, focusing specifically on the narrative verses in surah Al-Kahf. The results indicate a methodological gap between tafsir theory and practice. Conceptually, al-Qasimiy applies highly strict precautionary principles. In practice, he is dominantly consistent in holding to these rules by providing criticism of the quoted isra’iliyyat narratives. However, an inconsistency gap is also found when he adopts a lenient stance (mutasahil) by accepting isra’iliyyat stories without any critical remarks. These findings bring two significant implications for contemporary tafsir studies. First, the sharpness of al-Qasimiy’s analysis successfully maintains the credibility of his work as a primary reference in Qur’anic studies. Second, this inconsistency gap encourages academics to avoid blind imitation (taklid) of any tafsir work. This encourages a critical reading approach to test the consistency between methodological formulations and their tafsir results at a practical level.